Sejarah dan Dinamika Sosial Fiqih Reformis dan Fiqih Tradisionalis di Indonesia - Salam, Abd. (Program Pascasarjana UIN Sunan Ampel Surabaya, 2009)
This paper is aimed at describing the history and the social dynamics of the reformist and traditionalist fiqh in Indonesia. It first tries to show that since the 13th century Islam in Indonesia has largely been Sufi-oriented. It was only fairly recently that Islam in this country came into contact with figh especially after the return of Indonesian students from the Middle East toward the end of the 19th century. The puritan and reformist movements that prevailed in the Middle East at the time especially those under the patronage of Muhammad Abdul Wahhab and Jamaluddin al-Afghani inspired Muslims of this country to launch a similar reform in Indonesia. This reform movement received a somewhat strong opposition from the traditionalists since the beginning of the 20th century, hence the tension between the two currents of thought. This paper pays particular attention to this dynamic tension in the context of the contemporary historical and legal development in Indonesia.